Research on Strength and Durability of Concrete Manufactured with Artificial Sand - Ajay Kumar; Dr. Amarender Kadian (International Journal on Orange Technologies, 2022)
The use of synthetic sand in concrete has attracted the interest of numerous academics all over the world. The growing demand for fine aggregate for the needs of building is greater than the supply of limited natural sand that is currently available. The physical properties of naturally occurring river sand and man-made sand should be compared (M-sand). The current study focused on the M30, M40, and M50 mixtures. The modulus of elasticity (MOE) was calculated by altering the proportion of M-sand from 0 to 100%. To determine the optimal percentage of manufactured sand, the aforementioned mixes were also evaluated for sorptivity and impact resistance. Moreover, microscopic studies were performed using scanning electron microscopy (SEM) and electron dispersive spectroscopy (EDS). Yet, as concrete grade and M-sand content increased, sorptivity was found to decrease. Also, a comparison between experimental MOE values and IS code results was done. According to microscopic investigations, M-sand has an angular and rough surface in comparison to natural sand, which is thought to be the cause of the material's improved MOE and impact resistance as well as its decreased sorptivity.